Believe in Yahweh's Name as God Without Eternal Limitations, God Appears and God Almighty Great - Rudy Budiatmaja (Khazanah Theologia, 2022)
This research aims to provide instructions or guidance from spiritual mentors who believe in Jesus Christ related to how to call, mention the person of God with respect to Jesus Christ (Yahweh) and be worshiped as Savior, which consists of 3 (three) characteristics, namely: (1) the name YHWH is called the Eternal God ('Ä“l 'Ålam) , (2) the name YHWH is referred to as the visible God ('Ä“l rÅ'Ã®) , (3) the name YHWH is referred to as God as the Shepherd for His people ('El shadday) as a giver of life, protection and blessing. The method used is to draw conclusions that are explanatory (explanatory) and confirmatory as well as qualitative in the form of library research using content analysis methods. The results showed that the mention of Yahweh's name is known as the eternal God ('Ä“l 'Ålam), the God who appears to be always present ('Ä“l rÅ'Ã®) and the almighty/powerful God ('El shadday). Finally, it can be concluded that the three names Yahweh or EL are suitable and in accordance with the Hebrew phrases in the Bible and can be trusted for Christians to use them in daily life in facing all challenges or problems of life.